The dispositif of maternity: foucaultian gazes towards mother & daughter photographies - Batista da Silva, Irene Rodrigues (2024)
The article presents a discursive analysis of photographic images by the Lebanese-American artist Rania Matar, whose focus is on the functioning of motherhood as a dispositif of power, a reflection tool developed by Michel Foucault. The analyzed photographs framed statements in which mothers and daughters are positioned in the discourse, through processes of objectification and subjectivation, triggered by the aforementioned dispositif. The corpus brings together a set of photographs belonging to the photographer's portfolio, named Unspoken Conversations: mothers & daughters, published on the internet.